Heart rate reactivity to trauma-related imagery as a measure of PTSD symptom severity: Examining a new cohort of Veterans. (March 2018) - Castro-Chapman, Paula L.; Orr, Scott P.; Berg, John; Pineles, Suzanne L.; Yanson, Jessica; Salomon, Kristen
Abstract: For over three decades, there has been considerable research documenting increased physiological reactivity to trauma-related stimuli as a characteristic feature of posttraumatic stress disorder (PTSD). The present study explored the potential for physiological assessment to aid in defining and validating screening criteria for the presence of significant PTSD-related symptoms in a sample of OEF/OIF/OND Veterans seeking care in a VA post-deployment health clinic. Heart rate reactivity scores during the imagining phase of the script-driven imagery paradigm were compared across groups of individuals with and without probable PTSD diagnoses, as defined by PCL-IV cutoff scores ranging from 40 to 60. Significant differences were found for groups defined by PCL-IV cutoff scores of 50 and 60, with 50 producing the largest effect size. Diagnosing PTSD is made challenging by the presence of overlapping symptoms shared with other diagnoses, as well as by the necessity for patients to accurately report their symptoms. An objective physiological measure capable of accurately differentiating individuals with and without PTSD provides potential adjunctive diagnostic and treatment information to clinicians. The present findings support the validity of physiological reactivity during SDI as a NIMH RDoC measure that can be used in research and clinical applications assessing trauma-related symptom severity. Highlights: HR reactivity to trauma cues can assist with assessing PTSD symptom severity. A PCL-IV cutoff of 50 was indicative of more severe PTSD symptom severity. Adjusting for age, sex and body mass index did not alter findings. Adjusting for depression symptoms, which were strongly correlated with PTSD symptom severity, diminished HR findings. Depression may serve as a moderator between PTSD and HR reactivity.